2019
DOI: 10.1038/s41598-019-40214-4
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the complex role of GRAS transcription factors in the arbuscular mycorrhiza symbiosis

Abstract: To improve access to limiting nutrients, the vast majority of land plants forms arbuscular mycorrhizal (AM) symbioses with Glomeromycota fungi. We show here that AM-related GRAS transcription factors from different subgroups are upregulated during a time course of mycorrhization. Based on expression studies in mutants defective in arbuscule branching ( ram1-1 , with a deleted MtRam1 GRAS transcription factor gene) or in the formation of functional arbuscules ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 67 publications
(138 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, recent studies have shown that root developmental processes such as lateral root formation and root apical meristem activity, which are critical for endosymbiosis and are positively regulated by GA in Arabidopsis, are oppositely controlled in M. truncatula (Fonouni‐Farde et al ., 2019). The discovery and characterization of RAM1 (Wang et al ., 2012; Park et al ., 2015; Pimprikar et al ., 2016) and subsequent identification of many other GRAS transcription factors as central regulators of arbuscule development in plants forming arbuscular mycorrhiza started to change this picture (Floss et al ., 2013; Yu et al ., 2014; Xue et al ., 2015; Heck et al ., 2016; Hartmann et al ., 2019; Ho‐Plagaro et al ., 2019). And interestingly, several of these transcription factors specific for mycorrhiza development were shown to be absent in Arabidopsis, emphasizing the need to extend the studies of root development to other plants.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have shown that root developmental processes such as lateral root formation and root apical meristem activity, which are critical for endosymbiosis and are positively regulated by GA in Arabidopsis, are oppositely controlled in M. truncatula (Fonouni‐Farde et al ., 2019). The discovery and characterization of RAM1 (Wang et al ., 2012; Park et al ., 2015; Pimprikar et al ., 2016) and subsequent identification of many other GRAS transcription factors as central regulators of arbuscule development in plants forming arbuscular mycorrhiza started to change this picture (Floss et al ., 2013; Yu et al ., 2014; Xue et al ., 2015; Heck et al ., 2016; Hartmann et al ., 2019; Ho‐Plagaro et al ., 2019). And interestingly, several of these transcription factors specific for mycorrhiza development were shown to be absent in Arabidopsis, emphasizing the need to extend the studies of root development to other plants.…”
Section: Discussionmentioning
confidence: 99%
“…Initial evidence of the action of GRAS factors in mycorrhization processes emerged from a comparative study between the processes of nodulation in legumes, as well as mycorrhization in most plant species ( Hirsch et al, 2009 ; Liu et al, 2011 ). The discovery and characterization of the GRAS TF RAM1 (Required for Arbuscular Mycorrhization 1; Park et al, 2015 ; Rich et al, 2015 ; Xue et al, 2015 ; Pimprikar et al, 2016 ; Müller et al, 2020 ) and subsequent identification of many other GRAS transcription factors as central regulators of arbuscule development in plants forming arbuscular mycorrhiza ( Floss et al, 2013 ; Yu et al, 2014 ; Xue et al, 2015 ; Heck et al, 2016 ; Hartmann et al, 2019 ; Ho-Plágaro et al, 2019 ) point out the relevance of the GRAS family for mycorrhiza development.…”
Section: Gras Interactions and Am Symbiosis Regulationmentioning
confidence: 99%
“…Genome-wide characterization and expression studies of TF genes activated during AM in Petunia ( Rich et al, 2017 ), Lotus ( Xue et al, 2015 ), Medicago ( Hartmann et al, 2019 ) and tomato ( Ho-Plágaro et al, 2019 ), have revealed that the GRAS gene family is prominent among the AM-inducible TF genes in plants. Moreover, most of these AM-induced GRAS genes belong to the scarecrow-like (A and B), RAD1, and RAM1 subfamilies, which are absent in the whole non-AM host Brassicaceae family ( Cenci and Rouard, 2017 ), suggesting that these GRAS genes play a specific role during mycorrhization.…”
Section: Introductionmentioning
confidence: 99%
“…Angiosperm GRAS proteins can be divided into 8–17 subfamilies, with loss of members or subfamilies in some species (Pysh et al ., 1999; Cenci and Rouard, 2017). They play important roles in many physiological processes, including hormone (especially GA) signaling (Olszewski et al ., 2002; Heo et al ., 2011; Hauvermale et al ., 2012; Daviere and Achard, 2016), root and shoot development (Stuurman et al ., 2002; Schulze et al ., 2010; Engstrom et al ., 2011; Heo et al ., 2011; Zhang et al ., 2011), phytochrome A signaling (Bolle et al ., 2000; Torres‐Galea et al ., 2013), male gametogenesis (Morohashi et al ., 2003), starch biosynthesis (Cai et al ., 2017), root nodule and arbuscular mycorrhiza symbiosis (Kalo et al ., 2005; Smit et al ., 2005; Hirsch et al ., 2009; Yokota et al ., 2010; Battaglia et al ., 2014; Xue et al ., 2015; Hartmann et al ., 2019), as well as tolerance to drought and salt stresses (Fode et al ., 2008; Xu et al ., 2015; Li et al ., 2018; Zhang et al ., 2020). The tomato genome has 54 GRAS proteins, which can be divided into 13 subfamilies (Huang et al ., 2015; Niu et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%